2001
DOI: 10.1046/j.1198-743x.2001.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of inoculum size on the antibacterial activity of cefpirome and cefepime against Klebsiella pneumoniae strains producing SHV extended-spectrum β-lactamases

Abstract: The present study found that most SHV-producing klebsiellae have MICs of cefpirome that imply susceptibility at the moderate inoculum size, in spite of the fact that, according to the NCCLS, all ESBL producers should be considered resistant to all cephalosporins, independent of MIC values. With a high inoculum, most of the strains seemed to be resistant to both antibiotics. Furthermore, the bactericidal activities of cefpirome and cefepime against isogenic Escherichia coli strains producing SHV-2, SHV-4 and SH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
20
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 17 publications
3
20
0
1
Order By: Relevance
“…2. As anticipated from other previous investigations (1,3,6,9,12,20), the killing of piperacillin was considerably reduced as the baseline inoculum increased from 1 ϫ 10 5 to 1 ϫ 10 8 CFU/ml. Significant reduction in bacterial burden (Ͼ2-log drop at 24 h) was observed with 4ϫ MIC when the baseline inoculum was 1 ϫ 10 5 CFU/ml ( Fig.…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…2. As anticipated from other previous investigations (1,3,6,9,12,20), the killing of piperacillin was considerably reduced as the baseline inoculum increased from 1 ϫ 10 5 to 1 ϫ 10 8 CFU/ml. Significant reduction in bacterial burden (Ͼ2-log drop at 24 h) was observed with 4ϫ MIC when the baseline inoculum was 1 ϫ 10 5 CFU/ml ( Fig.…”
Section: Resultssupporting
confidence: 68%
“…Such a modeling approach could be used as a decision-support tool for dosing regimen design, and it may be used at different stages of drug development. It is often observed that killing could be more pronounced against a lower bacterial burden than with a higher bacterial burden (1,3,18). Capturing this phenomenon in a mathematical model would require a killing function dependent on bacterial burden.…”
mentioning
confidence: 99%
“…Factors that could contribute to these effects are the number, type, and amount of ␤-lactamases; outer membrane permeability; efflux; number and susceptibility of penicillin-binding protein targets; and phase of growth. Strain dependence has also been observed (1). In this work, we sought to correlate the NCCLS ESBL testing protocols and inoculum effects with levels and hydrolysis properties of ESBL and AmpC ␤-lactamases.…”
Section: Discussionmentioning
confidence: 99%
“…This so called "inoculum effect, " in which drug MICs increase dramatically in the presence of an increased bacterial load despite apparent initial susceptibility, has been observed in both in vitro and animal studies [25][26][27][28][29][30][31]. Highlighting one experience, Burgess and colleagues evaluated cefepime and meropenem against standard-and high-inoculum ESBL Klebsiella pneumoniae infections [32].…”
Section: Cefepimementioning
confidence: 99%